2012
DOI: 10.1159/000336196
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genome-Wide Pathway Association Analysis with INTERSNP

Abstract: Objectives: Pathway association analysis (PAA) tests for an excess of moderately significant SNPs in genes from a common pathway. Methods: We present a Monte-Carlo simulation framework that allows to formulate the main ideas of existing PAA approaches using a self-contained rather than a competitive null hypothesis. A stand-alone implementation in INTERSNP makes time-consuming communication with standard GWAS software redundant. By additional parallelization with the OpenMP API, we achieve a reduction in runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Our GDM approach is complementary in this case, as it allows for relative allelic responses to be simultaneously characterized across predictor variables. Approaches that characterize gene interactions may further elucidate the polygenic basis of environmental adaptation (e.g., Herold et al, 2012;Lee & Mitchell-Olds, 2012 Chauhan et al (2014Chauhan et al ( , 2016 (visual processing and thermal stress), while we found additional support for strong selection on genes involved in ion transport (V-ATPase) and other cellular processes.…”
Section: Broad Allelic Frequency Changes Across the Range Expansionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our GDM approach is complementary in this case, as it allows for relative allelic responses to be simultaneously characterized across predictor variables. Approaches that characterize gene interactions may further elucidate the polygenic basis of environmental adaptation (e.g., Herold et al, 2012;Lee & Mitchell-Olds, 2012 Chauhan et al (2014Chauhan et al ( , 2016 (visual processing and thermal stress), while we found additional support for strong selection on genes involved in ion transport (V-ATPase) and other cellular processes.…”
Section: Broad Allelic Frequency Changes Across the Range Expansionmentioning
confidence: 63%
“…Our GDM approach is complementary in this case, as it allows for relative allelic responses to be simultaneously characterized across predictor variables. Approaches that characterize gene interactions may further elucidate the polygenic basis of environmental adaptation (e.g., Herold et al., ; Lee & Mitchell‐Olds, ).…”
Section: Discussionmentioning
confidence: 99%
“…Multi-SNP approaches like interaction and pathway analysis were proposed [3] to detect the still unexplained portion of genetic disease risk. While Genome-wide interaction analysis has become computationally feasible [4], [5], by now only few, if any, replicable interactions have been found. In order to explain the phenomenon of missing evidence for interaction, Zuk et al [6] suggested that common diseases may follow so-called limiting pathway liability models (LPLMs).…”
Section: Introductionmentioning
confidence: 99%
“…are another issue that we will explore in greater depth using the example of INTERSNP (14,18), a popular software tool used for GWAS of case-control SNP data and quantitative traits. The algorithm behind INTERSNP belongs to the class of linear Euclidean measures and models relationships between genomic variables such as Y, X and non-genomic variables U as a linear regression (when variables U are assumed to be explicitly available as data -i.e.…”
Section: Errors Introduced By the Underlying Modelmentioning
confidence: 99%